2018
DOI: 10.3389/fpsyg.2018.01608
|View full text |Cite
|
Sign up to set email alerts
|

Avoidant/Restrictive Food Intake Disorder: A Longitudinal Study of Malnutrition and Psychopathological Risk Factors From 2 to 11 Years of Age

Abstract: Aim: To evaluate different types and degrees of malnutrition over time in a sample of children diagnosed with Infantile Anorexia (IA), based on the DC:0-3R criteria, and recently defined by DSM-5 as the first subtype of Avoidant/Restrictive Food Intake Disorder (ARFID), and to investigate the relationship between children’s severity of malnutrition and emotional/behavioral development, and mothers’ long-term psychopathological symptoms.Methods: A total of 113 children (58 boys, 55 girls), originally diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 39 publications
(63 reference statements)
1
36
0
7
Order By: Relevance
“…Both reported low BP, but only AN had lower systolic BP versus HC. Those with AN reported a higher prevalence of bradycardia and had lower heart rate on exam than ARFID, which might reflect more acute weight loss in AN (Keery et al, ; Lucarelli, Sechi, Cimino, & Chatoor, ; Norris et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Both reported low BP, but only AN had lower systolic BP versus HC. Those with AN reported a higher prevalence of bradycardia and had lower heart rate on exam than ARFID, which might reflect more acute weight loss in AN (Keery et al, ; Lucarelli, Sechi, Cimino, & Chatoor, ; Norris et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the mothers filled out the child behavior checklist (CBCL 1.5-5) [34] for the assessment of children's emotional-behavioral functioning and the Symptom Checklist-90-Revised (SCL-90-R) [35] for the assessment of their psychopathologic symptoms. These tools were chosen because they are very widely used in international research and proved their validity to capture a wide range of psychopathologic difficulties that can be experienced by mothers and children [17,36,37]. Moreover, mother-child feeding interactions were videotapes during a main meal (20-min videos) at the family home, based on a validated procedure [38,39] and in line with previous studies [25,40].…”
Section: Methodsmentioning
confidence: 99%
“…About one-third of participants in this study had ARFID; these patients may show less fear of being fat and body image distortion, which might account for the low scores for the disease-specific factor. Furthermore, several psychometric studies have shown that the patient’s emotional state or interpersonal relationships were more relevant to pathophysiology in children with ARFID than in children with typical AN [39, 40].…”
Section: Discussionmentioning
confidence: 99%